Kemampuan Siswa untuk Menghasilkan Gagasan Konsep Matematika Melalui Pedekatan SAVI Siswa Madrasah Ibtidaiyah - Samsul Bahri (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2020)
The ability of students to produce the idea of mathematical concepts is one of main objectives of mathematics education and important. This research is based on the problem of low students' ability in generating mathematical concept ideas. As an alternative to the problem, this research is conducced through the application of SAVI approach in mathematics learning. The idea of fundamental mathematical concepts used by students in finding formal mathematical forms are the context of fact and science through the SAVI approach (Somatics, Auditory, Visual, Intelectual). The purpose of this research is to know the ability of students to build ideas for mathematical concepts in fractional materials. The type of research used is descriptive qualitative research. Based on the results of the experiment the idea of mathematical concepts was used by students in MI in producing the idea of mathematical concepts on the operation of summation and fraction reduction. The this study found that of the study Show (1) showing every activity that has been designed, students use the idea of mathematical concepts in the learning process. (2) The application of SAVI learning approach has been able to improve the ability of MI students to produce the idea of mathematical concepts in fractional material. (3) The idea of mathematical concepts in the students was an earlycapacity of 85.4%, while the students had an early initial of 61.7%, while students campaigsed for a low increase in the idea of the mathematical concept not increasing.